Variasi Kosakata Bahasa Ibu dalam Pemerolehan Bahasa Anak Balita di Desa Marga Dauh Puri, Kabupaten Tabanan: Kajian Psikolinguistik - Adi Anggaraeni, Ni Made; Suparwa, I Nyoman (Humanis; Vol 23 No 2 (2019)DO - 10.24843/JH.2019.v23.i02.p06, 2019)
This research is entitled "Vocabulary of Mother Language Variations in Acquiring Toddler Language in Marga Dauh Puri Village, Tabanan Regency: Psycholinguistic Study." The purpose of this study was to find out vocabulary categories, word variations, and factors that influence mastery and acquisition of language variations given his mother to a toddler in Marga Dauh Puri Village, Tabanan Regency. The theory used is the theory of language acquisition proposed by Chaer, the theory of language teaching proposed by Simanjuntak, and the theory of child development proposed by Chaer. To achieve these objectives, several methods and techniques are used. The source of the data for analysis was the family that had a five-year-old child in the V illage of Marga Dauh Puri, Tabanan Regency. Furthermore, it was chosen by quota sampling technique. The results of this study are in the form of vocabulary taught by mothers to children including vocabulary categories such as noun categories, verbs, and adjective categories. The use of the dominant language taught is Balinese. Vocabulary variations include repetition and word variations. The dominant vocabulary variation used by mothers is word variation. Factors that influence the mastery and acquisition of vocabulary by children under five, are environmental factors, formal teaching factors, and age factors. The dominant factor influencing the mastery and acquisition of vocabulary by children under five in Marga Dauh Puri Village, Tabanan Regency is an age factor.